Left Ventricular Assist Device Inflow Cannula Angle and Thrombosis Risk. (April 2018) - Chivukula, Venkat Keshav; Beckman, Jennifer A.; Prisco, Anthony R.; Dardas, Todd; Lin, Shin; Smith, Jason W.; Mokadam, Nahush A.; Aliseda, Alberto; Mahr, Claudius
Abstract : Background: As heart failure prevalence continues to increase in the setting of a static donor supply, left ventricular assist device (LVAD) therapy for end-stage heart failure continues to grow. Anecdotal evidence suggests that malalignment of the LVAD inflow cannula may increase thrombosis risk, but this effect has not been explored mechanistically or quantified statistically. Our objective is to elucidate the impact of surgical angulation of the inflow cannula on thrombogenicity. Methods and Results: Unsteady computational fluid dynamics is used in conjunction with computational modeling and virtual surgery to model flow through the left ventricle for 5 different inflow cannula angulations. We use a holistic approach to evaluate thrombogenicity: platelet-based (Lagrangian) metrics to evaluate the platelet mechanical environment, combined with flow-based (Eulerian) metrics to investigate intraventricular hemodynamics. The thrombogenic potential of each LVAD inflow cannula angulation is quantitatively evaluated based on platelet shear stress history and residence time. Intraventricular hemodynamics are strongly influenced by LVAD inflow cannula angulation. Platelet behavior indicates elevated thrombogenic potential for certain inflow cannula angles, potentially leading to platelet activation. Our analysis demonstrates that the optimal range of inflow angulation is within 0±7° of the left ventricular apical axis. Conclusions: Angulation of the inflow cannula >7° from the apical axis (axis connecting mitral valve and ventricular apex) leads to markedly unfavorable hemodynamics as determined by computational fluid dynamics. Computational hemodynamic simulations incorporating Lagrangian and Eulerian metrics are a powerful tool for studying optimization of LVAD implantation strategies, with the long-term potential of improving outcomes.